Short promoters in viral vectors drive selective expression in mammalian inhibitory neurons, but do not restrict activity to specific inhibitory cell-types - Nathanson, Jason L.; Jappelli, Roberto; Scheeff, Eric D.; Manning, Gerard; Obata, Kunihiko; Brenner, Sydney; Callaway, Edward M. (Frontiers in Neural Circuits, 2009)
Short cell-type specific promoter sequences are important for targeted gene therapy and studies of brain circuitry. We report on the ability of short promoter sequences to drive fluorescent protein expression in specific types of mammalian cortical inhibitory neurons using adeno-associated virus (AAV) and lentivirus (LV) vectors. We tested many gene regulatory sequences derived from fugu (Takifugu rubripes), mouse, human, and synthetic composite regulatory elements. All fugu compact promoters expressed in mouse cortex, with only the somatostatin (SST) and the neuropeptide Y (NPY) promoters largely restricting expression to GABAergic neurons. However these promoters did not control expression in inhibitory cells in a subtype specific manner. We also tested mammalian promoter sequences derived from genes putatively coexpressed or coregulated within three major inhibitory interneuron classes (PV, SST, VIP). In contrast to the fugu promoters, many of the mammalian sequences failed to express, and only the promoter from gene A930038C07Rik conferred restricted expression, although as in the case of the fugu sequences, this too was not inhibitory neuron subtype specific. Lastly and more promisingly, a synthetic sequence consisting of a composite regulatory element assembled with PAX6 E1.1 binding sites, NRSE and a minimal CMV promoter showed markedly restricted expression to a small subset of mostly inhibitory neurons, but whose commonalities are unknown.